(untitled) (Journal of Kidney Cancer, 2026)
von Hippel–Lindau (VHL) disease, an autosomal dominant inherited disorder resulting from mutations in the VHL gene, is known to be asso-ciated with the development of neuroendocrine tumors (NET) in various organs, including the adrenal gland, pancreas, and paraganglion. However, the development of gastric NET (gNET) in VHL disease has not been reported. Limited studies have suggested that clear cell change is a distinctive feature of VHL-associated tumors. Herein, we first report a case of a patient with VHL syndrome who presented with a gNET showing clear cell change, an unusual morphological characteristic of gNET, and harbored a pathogenic germline VHL mutation (c.351 G>T). The patient underwent surgical treatment for retinal hemangioblastoma, gNET, and renal cell carcinoma, in addition to receiving endocrine therapy and antiangiogenic drugs. The patient survived for 17 years. Our case highlights the possibility of VHL-associated NET development in uncommon locations. Further studies are required to elucidate the correlation between VHL mutation sites and the clinical manifestation of the disease.